The complete genome sequence of the pathogenic intestinal spirochete Brachyspira pilosicoli and comparison with other Brachyspira genomes. - Phatthanaphong Wanchanthuek (Public Library of Science (PLoS), 2010)
Background The anaerobic spirochete Brachyspira pilosicoli colonizes the large intestine of various species of birds and mammals, including humans. It causes "intestinal spirochetosis", a condition characterized by mild colitis, diarrhea and reduced growth. This study aimed to sequence and analyse the bacterial genome to investigate the genetic basis of its specialized ecology and virulence. Methodology/principal findings The genome of B. pilosicoli 95/1000 was sequenced, assembled and compared with that of the pathogenic Brachyspira hyodysenteriae and a near-complete sequence of Brachyspira murdochii. The B. pilosicoli genome was circular, composed of 2,586,443 bp with a 27.9 mol% G+C content, and encoded 2,338 genes. The three Brachyspira species shared 1,087 genes and showed evidence of extensive genome rearrangements. Despite minor differences in predicted protein functional groups, the species had many similar features including core metabolic pathways. Genes distinguishing B. pilosicoli from B. hyodysenteriae included those for a previously undescribed bacteriophage that may be useful for genetic manipulation, for a glycine reductase complex allowing use of glycine whilst protecting from oxidative stress, and for aconitase and related enzymes in the incomplete TCA cycle, allowing glutamate synthesis and function of the cycle during oxidative stress. B. pilosicoli had substantially fewer methyl-accepting chemotaxis genes than B. hyodysenteriae and hence these species are likely to have different chemotactic responses that may help to explain their different host range and colonization sites. B. pilosicoli lacked the gene for a new putative hemolysin identified in B. hyodysenteriae WA1. Both B. pilosicoli and B. murdochii lacked the rfbBADC gene cluster found on the B. hyodysenteriae plasmid, and hence were predicted to have different lipooligosaccharide structures. Overall, B. pilosicoli 95/1000 had a variety of genes potentially contributing to virulence. Conclusions/significance The availability of the complete genome sequence of B. pilosicoli 95/1000 will facilitate functional genomics studies aimed at elucidating host-pathogen interactions and virulence.